AK112 (PD-1/VEGF-a bispecific antibody) combined with chemotherapy in locally advanced pancreatic cancer: a case report - Yan, Jiuliang; Dong, Hanguang; Wu, Chuntao; Gu, Haitao; Qi, Zihao; Chen, Tao; Hu, Beiyuan; Zhou, Huijiang; Long, Jiang (Frontiers in Oncology, 2026)
BackgroundPancreatic ductal adenocarcinoma (PDAC) is one of the most malignant tumors. Most patients are diagnosed at advanced or metastatic stages, losing the opportunity for curative surgery. Current systemic treatments for pancreatic cancer remain suboptimal.Case summaryA 68-year-old female presented with upper abdominal pain. Imaging revealed a pancreatic mass, prompting an exploratory laparotomy. Intraoperative frozen section pathology identified metastatic adenocarcinoma nodules near the hepatic artery. The patient was subsequently evaluated and enrolled in a clinical trial. The treatment regimen comprised AG chemotherapy (nab-paclitaxel and gemcitabine) combined with AK112 (a novel bispecific antibody). After 13 administrations of AG chemotherapy and 9 infusions of AK112, imaging evaluation demonstrated partial tumor regression. A multidisciplinary team (MDT) assessment deemed the lesion potentially resec]. The exploratory laparotomy confirmed resectability, and a total pancreatectomy was performed. Postoperative pathology confirmed moderately differentiated pancreatic ductal adenocarcinoma with focal degenerative changes. During postoperative treatment, wound exudate suggestive of intestinal leakage prompted surgical intervention on June 12, 2023. Adjuvant therapy resumed after wound healing but was discontinued in September 2023 due to recurrent incision leakage. Maintenance therapy with tegafur was initiated thereafter. Unfortunately, the patient died of acute myocardial infarction on August 4, 2024.ConclusionThe combination therapy of AK112 and AG achieved good results in this case, but the broader efficacy of this regimen across the pancreatic cancer population awaits validation through large-scale clinical trials. The ongoing trials are highly anticipated, as successful results could establish AK112 as a novel therapeutic strategy for pancreatic cancer.